De Vliekerwaterlossing op landgoed Vliek te Ulestraten: Bron van inspiratie voor een waterhuishoudkundige uitdaging - Hovens, Frank (Studies over de sociaaleconomische geschiedenis van Limburg, 2025)
The southern, hilly part of the province of Limburg in the Netherlands is likely to face increased occurrences of excessive rainfall and muddy streams in the future due to climate change. Authorities are seeking ways to mitigate these impacts, such as improving the soil’s capacity to retain water. The Vliek estate in Ulestraten (municipality of Meerssen, near Maastricht) is identified as a site with the potential to contribute to this effort. A small stream, the Vliekerwaterlossing, fed by several wells, flows through the estate. Given Vliek’s historical significance, any decision must carefully consider its monumental values. Historical research is essential to understand the current situation and may offer creative solutions. This paper examines the history of the Vliekerwaterlossing and its fundamental role in the estate’s design, with the aim of guiding decision-makers toward informed choices.